Estruturas de governança e poder de comprador em sistemas agroalimentares e sistemas diferenciados da carne bovina do estado do Paraná - Santos, Rejane Heloise dos (2017)
The Brazilian Agri-food System (AG) of bovine meat presents a prominent world position and expressive numbers. However, it also presents historical problems of coordination failures, distrust and opportunistic behavior. Aggravating these diversities, there is the assumption that the buyer link may present buyer power to the detriment of the producer link. Regarding the consumer link, it has been increasingly presenting higher quality demands, causing the industry to invest in quality attributes, in order to add value to the product. Thereby, commodity beef becomes unfeasible for many producers, resulting in different types of arrangements which aim product differentiation as the Differentiated Agri-Food Systems (DAS's), that coexist with the conventional AG's. However, in spite of these cooperative arrangements, failures due to the asymmetry of power can prevail. Thus, the present study aimed to understand the influence of buyer power on transactions involving producers and buyers in the AG of beef in the state of Paraná and in a DAS of beef in the same state. For this purpose, a qualitative, descriptive study with sectional cut was carried out, involving the collection of primary and secondary data. Based on the precepts of Transaction Cost Economics (TCE), Measurement Cost Economics (MCE) and Buyer Power theory, the research involved the collection of primary and secondary data. Data collection was performed through semi-structured interviews with producers of the conventional and differentiated systems, with the manager of DAS chosen and key agents. Primary data also involved documents provided by respondents. Data analysis was performed through content analysis (BARDIN, 1979), involving the ATLAS/ti software. The results showed the existence of buyer power in both systems. In the conventional system, the governance structure happens via the market, In disagreement with the precepts of TCE, but in line with the precepts of the MCE. Buyer power, although it does not manifests itself as expressed in the literature of buyer power, generates unilateral dependence on the links, which are aggravated by the lack of coordination and marketing conditions, contributing to render the transactions, somehow, favorable to the buyer. Thus, the structure of governance via the market has its efficiency reduced, by presenting transaction costs and limits the benefits to one of the parties, the producer, who becomes subject to the terms imposed by the buyer. With respect to the differentiated system, the relationship based on bilateral dependence makes the transactions important for both parties, occurring the alignment with the precepts of the TCE and MCE. However, in this system, the hybrid governance structure is efficient, providing the reduction of uncertainties and elevation of trust, allowing savings in transaction and measurement costs. Therefore, even with the buyer power noticed in both systems, in the conventional system this power does not manifest itself as expressed in the literature of buyer power, but under more favorable conditions to buyers in the transaction. In the differentiated system, although there are manifestations of buyer power expressed in contractual obligations to producers, such impositions pursue the organization of the DAS, not concerning opportunistic actions and not aiming to generate differential gains for buyer.